Adsorption and Purification of Zinc in Mining Wastewater Using Microbial Immobilization Technology - Wang, Shouwu; Chen, Wenbin (Asian Journal of Chemistry, 2013)
The Leptospirillum ferrooxidans has been selected and cultivated from mine area and applied in treatment of Zn2+-containing wastewater in the laboratory and real Zn2+-containing wastewater. The principle of its adsorption process was probed. The results show that the main factors which affect the zinc uptake are pH value, ways of pretreatment, contacting time, co-existing ions, Leptospirillum ferrooxidans concentration in solutions, etc. It was able to adsorb Zn2+ efficiently. After adsorption steps of the treatment, the concentration of Zn2+ in solution met the standard for treating wastewater. After adsorption treatment of containing zinc mine wastewater, the concentration of zinc ions reaches the first class of irrigation water quality standards.